Impedance Meter Berbasis Field Programmable Gate Array (FPGA) Untuk Optimasi Respons Pengukuran Amplitudo Dan Beda Fasa - Santoso, Ardhi Wicaksono; Rifai, Isnan Nur; Sumanto, Budi; Purnomo Aji, Alief (Fakultas Teknik Universitas Muria Kudus, 2025)
The Impedance Meter (IM) has become essential in exploring the electrical properties of materials, biological systems, and electrochemical processes. Measuring amplitude and phase difference is central to characterizing these materials and systems. This research aims to develop an amplitude and phase difference measurement system using Field-Programmable Gate Array (FPGA) technology with a cross-correlation method. Validation system is conducted by measuring the high pass response which consist of resistor and capacitor. Performance evaluation covers speed, accuracy, and system responsiveness to frequency variations. Based on the measurement and validation results, the following conclusions are drawn: The number of buffers in the data sampling process can impact accuracy and processing time. It takes 0.26 seconds for 100 phase difference measurements with a buffer count of 2000. Compared to mathematical analysis, amplitude measurements have an average error of 0.035 volts (3.5%) with a maximum error of 0.048 volts (4.8%). Phase difference measurements have an average error of 0.22° with a maximum error of 1.26°. While if compared to an oscilloscope, amplitude measurements show an average error of 0.002 volts (0.2%) with a maximum error of 0.012 volts (1.2%). Phase difference measurements show an average error of 0.18° with a maximum error of 0.86°. Mathematical analysis provides important theoretical understanding, while validation with an oscilloscope offers more accurate and realistic information under practical conditions, considering component non-idealities.